Two early witnesses to the formation of the Miqra Bikurim Midrash and their implications for the evolution of the Haggadah text - Rovner, Jay (Hebrew Union College annual / Jewish Institute of Religion, 2004)
The midrashic elaboration of the exodus narrative encapsulated in Deuteronomy 26:5-8 is basic to the Passover Haggadah liturgy. Because m.Pesaḥ. 10:4 prescribes the expounding of that passage (doresh meʾarami ʿovedʾavi), it is generally assumed that the midrash found in standard, i.e., Babylonian, medieval European, and modern Haggadahs dates in large part to the tannaitic period, even though the corresponding Eretz-Israel version contains very little midrashic adornment. A manuscript fragment from the Cairo Genizah reveals that the standard text began with precious little midrashic text as well, and a second one provides an equally brief, but very different, alternative showing a process of augmentation that, in combination with the first version, would eventually lead to the fulsome standard midrash. The latter did not really evolve until post-talmudic (geonic) times. The unique style of the full midrashic composition will be examined to show that liturgical concerns, as well as midrashic ones, combined to produce the standard midrash. Appendix A provides a synoptic table of early Haggadah midrash-texts in comparison with the standard one. Readings in the fragments indicative of an early stage in the development of the Haggadah fragments treated herein are noted in Appendix B, where the texts are transcribed in full. A claim for a possibly tannaitic Haggadah midrash is examined in Appendix C.